A STUDY ON THE REPRODUCTIVE BIOLOGY OF BOLEOPHTHALMUS BODDARTI FROM MUMBAI REGION - Chandran, Rejani; Jaiswar, A. K.; Jahageerdar, Shrinivas; Poojary, Nalini; Chakraborty, S. K. (Journal of Indian Fisheries Association, 2014)
Boleophthalmus boddarti (Pallas, 1770) is an important fish species, both as food for the populace as well as baits for industrial or offshore fisheries. The present study was conducted to understand the reproductive biology of the species with special reference to recruitment potential. A total of 129 female species were collected from Bhayandar, Kalyan and Vasai creeks around Mumbai, India. The study revealed that about 1.7% of the body mass of female fish was used in gonad development. The absolute fecundity of the species was estimated to be 4778Â±1.18 ova with the diameter ranging from 0.012 mm to 0.892 mm. Histological study of the ovary indicated five stages of maturity: immature, maturing, late maturing, ripe and spent. The impact of pollution could be recorded in the form of fat accumulation in the liver and variation with respect to fecundity was noticed among different creeks.Â Key words: Reproductive biology, Boleophthalmus boddarti, Mumbai region.